Determination of the residual resource of carrying metal frames of cars of hopper dosers and dumpkars (dumpers) based on the results of technical diagnostics and typical tests (Transport systems and technologies, 2020)
Most of the cars of hopper dosers and dumpkars (dumpers)  on the railways of ukraine have a service life that significantly exceeds that established by the manufacturer. The article studies the residual life of load-bearing metal structures of hopper dosers and dumpkars (dumpers)  based on the results of technical diagnostics and type tests. The analysis of the ratio of the actual thickness of the spinal beam of cars to the nominal values. Possible places of occurrence of typical defects in hopper dosers and dumpkars (dumpers) are determined. it is concluded that the state of the supporting metal structures of cars after long-term operation does not approach the limit. the obtained practical and theoretical results allow us to develop a set of measures to assess the residual life of the bearing metal structures of hopper dosers and dumpkars (dumpers).
Keywords: residual life, hopper dosers, dumpkars (dumpers), technical diagnostics, type tests, operational characteristics, carrying metal structure